Scientific principles of determination of efficiency of running a separate passenger train - Drebot, Kh. V.; Barash, Yu. S. (Science and Transport Progress, 2012)
Determination of economic efficiency of the management of separate passenger train depends on the correct calculation of sum of charges on carrying passengers by a concrete train. Material is given in relation to determination of charges on running a separate passenger train including the passenger, locomotive, motor-car and infrastructural components. It allows correctly setting profitability or unprofitableness of train and the same to promote profitability of passenger trains in distant traffic.